Instagram in ESL classroom - Mansor, Noraien; Abd Rahim, Normaliza (Serials Publications, 2017)
The canvas of language teaching and learning has experienced major changes in the decade of emerging technologies. The use of various applications through computers and smartphones have paved the way for ESL (English as a Second Language) instructors to innovatively shape their strategies and approaches in language teaching and learning. Students of today's world are complacent in a dynamic, digital and social world with a wide range of ever changing technologies. In fact, by applying social media in language classroom, namely facebook, instagram, blogs and twitter, learners will be highly motivated to interact socially with their peers. As such, instagram has a beneficial characteristic as it falls on the category of social networking and the main source of networking is communication. This study seeks to reveal the students experience in applying the tool to motivate as well as enhance their interest to participate and interact with their peers. It investigated students' participation in online discussions and their feedback on the use of instagram as the platform for language learning activity. The results of the study revealed that instagram is no doubt an effective tool for students' interactions especially in the discussion of their task-related activity. The subjects involved seemed to be more motivated and they love to participate and interact with their peers as instagram has fueled their interest towards learning. It is hoped that further research will focus on some essential tools of instagram such as special intelligence, linguistic intelligence and interpersonal intelligence that could benefit for educational purposes.